Estudio de la conducta sexual y calidad seminal en fresco en 3 grupos raciales en equinos - Montalvo Illescas, Milton Alejandro (2019)
The present investigation was carried out in Canton Quilanga and was oriented to determine the sexual behavior and characteristics of fresh equine semen in horses of diverse racial groups, we worked with the Arab, Mestizo and Criollo breeds. Sexual behavior was evaluated before, during and after riding by observing the symptoms of sexual behavior. For the seminal evaluation, 3 collections were made in each of the racial groups at intervals of one week and the following microscopic and macroscopic variables were studied. In the macroscopic evaluation, the physical characteristics were observed: color, density, pH. While in the fresh microscopic evaluation, motility, vigor, morphology and sperm concentration were evaluated. An analysis of variance was performed, and a 5% Fisher LSD test was applied. The results show that there was no significant statistical difference in vigor, minor morphological defects, pH and color. A statistically significant difference (p: 0.05) was observed in the volume, with the Creole breed having the highest volume (80cc), compared to the rest of the breeds where 45 cc was obtained in the Mestiza race and 36.66 cc in the Arab race. Motility registered the Arab race with the highest percentage of 68.33% while the Mestiza breed obtained 58.33% and the Creole breed 56.66% In the concentration the Mestizo breed had a higher concentration of 137.33 million / ml, the Arabian breed obtained 131.66 million / ml, while the Creole breed obtained 84.6 million / ml. In the major defects the Arab race had a lower percentage with 7.33%, while the Mestiza breed had 16.33% and the Creole breed 16.86% It is concluded that if While the Creole breed is related to a better sexual behavior, which can be determined by the type of management of extensive form that the animal has, in terms of the seminal characteristics these animals had a lower seminal quality, the reason may depend on factors such as nutrition, management, upbringing, physical build, consanguinity, to which this population is subject in relation to the other racial groups. Keywords: races, sexual behavior, stallions, equine semen, seminal evaluation